Market power and information revelation in dynamic trading - Piero Gottardi; Roberto Serrano (Brown University, Department of Economics, 2002)
We study a strategic model of dynamic trading where agents are asymmetrically informed over common value sources of uncertainty. There is a continuum of uninformed buyers and a finite number of sellers, some of them informed. When there is only one seller, full information revelation never occurs in equilibrium and the only information transmission happens in the first period. The outcome with n sellers depends both on the structure of sellers' information and, more importantly, on the intensity of competition among them allowed by the trading rules. With intense competition (absence of clienteles), information is fully and immediately revealed to the buyers in every equilibrium for n large enough, both when all sellers are informed and when only one seller is informed. On the other hand, with a less intense form of competition (presence of clienteles), we always have equilibria where information is never fully revealed, whatever the number of sellers. Moreover in this case, when only one seller is informed, for many parameter configurations there are no equilibria with full information revelation, for any n.
Keywords: C72; C78; D82; D83; 330; asymmetric information; information revelation; dynamic trading; oligopolistic competition; clienteles; Asymmetrische Information; Monopol; Oligopol; Informationsverhalten; Marktmacht; Theorie